DEPENDENCE OF FORMATION OF CORN HARVEST ON FORMS AND RATES OF PHOSPHORUS FERTILIZERS - B. Nabiev (Scholars Digest Publishing, 2023)
The application of phosphorus fertilizers in the form of polyphosphates provided a better yield of corn grain, like unwashed soil. An increase in the content of nitrates was not detected in corn grain and green mass, i.e. The resulting products are environmentally friendly and can be used for food and animal feed.
Keywords: corn, plants, green mass, leaves, stem, crop, fertilizers, soil, polyphosphate.